ANALISIS TINDAKAN SOSIAL MAX WEBER DALAM TRADISI PEMBACAAN KITAB MUKHTASHAR AL-BUKHARI (Studi Living Hadis) - Alis Muhlis; Norkholis Norkholis (Jurnal Living Hadis, 2016)
The tradition of reading the book of Mukhtashar Al-Bukhari is one of the welcoming traditions to the holy month Ramadan, conducted every month per year at Islamic Boarding School At-Taqwa Yogyakarta. The tradition is fully practiced on Rajab, a month before Ramadhan at lunar based calendar. This research utilizes four types of Max Weber’s social action theory, those are traditional action, affective action, instrumental rationality, and value rationality. The result found that: first, according to the traditional action, the people are willing to preserve the tradition which has been inherently practiced. Second, the affective action shows that the people are emotionallyboundedto the ulama’ figures (salafu as-shalih) and the timing (Rajab). Third, instrumental rationally the pointed out that people at At-Taqwa are capable of practicing the tradition due to the capacity on both human resource and finance. Fourth, on value rationality they are encouraged to achieve barokah by following and preserving the tradition of salafus shalih.